2015
DOI: 10.1185/03007995.2015.1034095
|View full text |Cite
|
Sign up to set email alerts
|

Persistence with opioid treatment in Germany in patients suffering from chronic non-malignant or cancer pain

Abstract: Our study showed that persistence with opioid treatment is associated with cancer pain, chronic comorbidities and depression, while younger age and chronic non-malignant pain (especially due to back pain) increase the possibility of opioid discontinuation. It will be the task of future studies to assess reasons for opioid discontinuation in more detail, which is an important step towards improving patient care and health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
2
2
0
1
Order By: Relevance
“… 14 , 16 , 17 After 36 months of follow-up, treatment adherence was low (21.0%). Kostev et al found that in a large cohort of patients (n=32,158) with chronic pain, 32 adherence to opioids was low; 69% of patients discontinued treatment per year of follow up, similar to our study (64%). In the series analyzed in this research, opioid use did not result in a substantial reduction in pain and had no direct effect in reducing days of sick leave.…”
Section: Discussionsupporting
confidence: 89%
“… 14 , 16 , 17 After 36 months of follow-up, treatment adherence was low (21.0%). Kostev et al found that in a large cohort of patients (n=32,158) with chronic pain, 32 adherence to opioids was low; 69% of patients discontinued treatment per year of follow up, similar to our study (64%). In the series analyzed in this research, opioid use did not result in a substantial reduction in pain and had no direct effect in reducing days of sick leave.…”
Section: Discussionsupporting
confidence: 89%
“…After 36 months of follow up, treatment adherence was low (21%). Kostev found that in a large cohort of patients (n=32,158) with chronic pain [30], adherence to opioids was low; 69% of patients discontinued treatment per year of follow up, similar to our study (64%). In the series analyzed in this research, opioid use did not result in a substantial reduction in pain and had no direct effect in reducing days of sick leave.…”
Section: Discussionsupporting
confidence: 88%
“…Kostev et al evaluated the persistence of opioids in a large cohort of patients ( n = 32,158) who were treated for chronic pain. 35 As of the following year, 69.0% had discontinued medication. The authors concluded that adherence to opioids was associated with chronic comorbidity and depression, whereas younger subjects with chronic noncancerous pain (back osteoarthritis) increased the likelihood of opioid discontinuation.…”
Section: Discussionmentioning
confidence: 99%